Por uma filosofia transvalorativa: a crítica da consciência moderna em Nietzsche - Collares, Regiane Lorenzetti (Universidade Federal de São Carlos, 2010)
At foreground, this research aims to seek the argumentative links that connect the critique of modern consciousness with the development of a project about Revaluation of All Values in the philosophy of Nietzsche. By addressing two problematic aspects of modern consciousness, Bewusstsein (reflexive consciousness) and Gewissen (conscience), the nietzschian philosophy, from the demarcation of the phenomenon of decadence in modern culture, suggests a new or second consciousness (ein neues Gewissen or ein zweites Bewusstsein) achieved at the expense of listening the truths that have become mute for moral imperatives of modern thought. So in plane parallel to the critical path made by Nietzsche, we also intend to investigate the content of this new or second consciousness in the last period of his philosophy and if there would be no inconsistency in restore something that was heavily criticized in the whole project of Revaluation. From these research plans, we intend to follow the formulations of a philosopher self-appointed psychologist, in which the body is taken as a guide of a critical suspicion that modern Bewusstsein, as the example of consciousness legitimized by Descartes and Kant, is involved in dangerous moral prejudices, and also distrust that the culture of his time was sick by virtue of the deepening of a consciousness that is truly an effect of surface.
Keywords: Filosofia alemã; Transvaloração; Consciência (Filosofia); Nietzsche, Friedrich Wilhelm, 1844-1900; CIENCIAS HUMANAS::FILOSOFIA